Pengaruh Struktur Modal Terhadap Profitabilitas Perusahaan Sektor Infrastruktur yang Terdaftar Di Bursa Efek Indonesia Tahun 2021-2023 - Gilang; Feriyanto, O (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
This study aims to analyze the effect of capital structure on profitability in infrastructure sector companies listed on the Indonesia Stock Exchange (IDX) in the 2021-2023 period. The capital structure in this study is measured using the debt to equity ratio (DER), while profitability is measured using Return on Asset (ROA). The research sample consisted of 55 infrastructure sector companies that met the selection criteria. Data were analyzed using simple linear regression. The results showed that the capital structure had a positive and significant effect on the profitability of infrastructure sector companies listed on the IDX in the 2021-2023 period.